Pendidikan Toleransi Berbasis Pembelajaran Kontekstual Kearifan Lokal Masyarakat - Imam Sofii; Yunus Salik (IAIN Manado, 2022)
Tolerance Education Based on Local Wisdom Contextual Learning. This research uses the ethnographic method. Interview technique, interviewed informants came from several groups. Researchers also interviewed 6 community leaders. The social relations in the Sukamaju community show a harmonious multiethnic social relationship. The role of local Luwu culture cannot be separated from multiethnic harmony. As a newcomer, the Sukamaju transmigration community always prioritizes peace. Local wisdom in Tana Luwu for example; Sipakatau means humanizing each other, Sipakalebbi means mutual respect, Sipakaingge 'which means reminding each other of Sipakatou (an expression of mutual love). Cultural values are the glue for the creation and maintenance of religious harmony in Tana Luwu. The value of local wisdom in Tana Luwu is in line with the values of pluralism that grow and develop in Indonesia